Effects of substance P on carotid chemoreceptor activity in the cat. - McQueen, D S (1980)
1. The influence of substance P (SP) on spontaneous chemosensory discharge and on responses of the carotid chemoreceptors to various drugs has been investigated in pentobarbitone anaesthetized casts in which chemoreceptor activity was recorded from the peripheral end of a sectioned sinus nerve. 2. After an initial slight inhibition during the first 5--15 sec following the injection, SP (0.1--100 microgram I.A.) caused a dose-related increase in discharge which lasted for 45--300 sec in artificially ventilated cats, discharge being increased by about 50% on average. The increase was of shorter duration when the animals were allowed to breathe spontaneously. 3. The delayed increase in discharge was not secondary to the hypotension caused by SP, nor was it entirely due to changes in bronchomotor tone resulting from direct or indirect actions of SP, although such changes contributed to the response. It was not possible to determine whether the excitation was due to a direct effect of SP on the chemoreceptors. 4. Chemosensory excitation evoked by NaCN (5 microgram I.A.) was potentiated during I.A. infusions of SP and also 10--20 min after SP (10 microgram I.A.) had been injected. In contrast, responses to ACh (50 microgram I.A.) were inhibited. These effects may be due to a nicotinic-blocking action of SP on the carotid chemoreceptors. It was also found that the inhibitory action of dopamine (5 microgram I.A.) was reduced during SP infusion whereas that of 5-HT (10 microgram I.A.) was potentiated. 5. A sample of crude SP had effects on spontaneous chemoreceptor discharge and responses to NaCN and ACh which were qualitatively similar to those obtained using synthetic SP. 6. The physiological significance of the results is discussed and it is concluded that the interpretation depends upon whether or not SP is present in the cat's carotid body.